2019
DOI: 10.1177/0022427819874862
|View full text |Cite
|
Sign up to set email alerts
|

Discretion and Disparity under Sentencing Guidelines Revisited: The Interrelationship between Structured Sentencing Alternatives and Guideline Decision-making

Abstract: Objectives: We argue that the reasons court actors conform to or depart from sentencing guideline recommendations likely vary depending on whether the decision involves an alternative sanction or incarceration and that these reasons may have consequences for ethnoracial disparities in the sentencing of defendants and how these disparities are understood. Method: We use recent (2012–2016) Pennsylvania sentencing data to examine (1) the relationship between defendant race/ethnicity and court actors’ decisions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…These relationships are persistent across both adult (Bontrager et al, 2005; Johnson & DiPietro, 2012; Painter‐Davis & Ulmer, 2020; Schlesinger, 2013) and juvenile populations (Anderson, 2015; Armstrong & Rodriguez, 2005; Caudill et al, 2013; Cochran & Mears, 2015; Maggard, 2015; Rodriguez, 2013) and are particularly salient for earlier decision points, such as diversion (Claus et al, 2017). In a systematic review of the literature on race and the punishment of juvenile offenders, Engen et al (2002) found evidence of an impact of race across multiple studies, and in particular, that these effects were stronger in studies that examined earlier decision points in the justice process, such as arrest.…”
Section: Relevant Literaturementioning
confidence: 99%
“…These relationships are persistent across both adult (Bontrager et al, 2005; Johnson & DiPietro, 2012; Painter‐Davis & Ulmer, 2020; Schlesinger, 2013) and juvenile populations (Anderson, 2015; Armstrong & Rodriguez, 2005; Caudill et al, 2013; Cochran & Mears, 2015; Maggard, 2015; Rodriguez, 2013) and are particularly salient for earlier decision points, such as diversion (Claus et al, 2017). In a systematic review of the literature on race and the punishment of juvenile offenders, Engen et al (2002) found evidence of an impact of race across multiple studies, and in particular, that these effects were stronger in studies that examined earlier decision points in the justice process, such as arrest.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Second, only felony offenses were included in the analysis. Following prior research, only the most severe offense committed by an offender within a judicial proceeding is included in the analysis (Cassidy & Rydberg, 2019; Painter-Davis & Ulmer, 2019; Steffensmeier et al, 2017). Finally, cases missing information on key variables were also excluded from the analyses (3.8%).…”
Section: Methodolgymentioning
confidence: 99%
“…2. Recent work utilizing the PCS data has opted to control for the presumptive sentence length rather than the offense gravity score because the former produced less multicollinearity (Steffensmeier et al, 2017;Painter-Davis & Ulmer, 2020).…”
Section: Authors' Notementioning
confidence: 99%